Analysis of the Impact of Economic Growth on Income Inequality and Poverty in South Africa: The Case of Mpumalanga Province - Niyimbanira, Ferdinand (International Journal of Economics and Financial Issues, 2017)
The aim of this article is to estimate the impact of economic growth on income inequality and poverty using data from the Mpumalanga Province in South Africa. Theoretically, it can be argued that there is a negative relationship between the Gini coefficient and economic growth, but evidence shows that it is not always the case. The same argument can be reasoned for economic growth and poverty. The purpose of this paper is to establish whether there is empirical evidence of such relationships. Furthermore, the paper examines the extent to which such nexuses are evident in South Africa with particular reference to Mpumalanga Province. The Gini coefficient is used as a proxy for income inequality. The method of analysis used is the fixed effect and pool regression models with secondary data from all 18 local municipalities in Mpumalanga. The results have demonstrated that economic growth reduces poverty but not income inequality. The findings of this study have implication for policy makers to design strategies of reducing income inequality in South Africa. The study concludes by proposing socio-economic measures that could enhance economic growth and improve human development in a knowledge-based economy. Keywords: Economic growth, Income inequality, Poverty, South Africa JEL Classifications: I30, O110